Innovations in teaching and learning: Exploring the perceptions of the education sector on the 4th industrial revolution (4IR) - Adekunle Oke; Fatima Araujo Pereira Fernandes (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Business operations are undergoing drastic changes due to the disruptive effects of technology innovations; however, there is insufficient knowledge regarding the acceptability and consequences of the fourth industrial revolution (4IR) in the education sector. Using the Unified Theory of Acceptance and Use of Technology (UTAUT), this study explores the readiness of the education sector for 4IR. We adopted face-to-face semi-structured interviews to explore the views of 33 key stakeholders in the education sector, to understand the readiness and acceptability of 4IR in the sector. Findings show that the education sector, especially in Africa, is unprepared for 4IR, although there are indications for opportunities to harness the potential of the much-anticipated 4IR. Moreover, our study demonstrates a mutual symbiotic relationship between the education sector and technology innovations. The findings show that 4IR can facilitate students' learning experience and transforms the workplace, although there is a need to assess the learning environment, to understand the facilitators and barriers to 4IR diffusion. The findings indicate the opportunity for the education sector to harness the innovations associated with 4IR through research and teaching to enhance learners' experience; however, this may require a significant improvement in education curricula, as well as investments. The findings contribute to the theory and practice of technology in education and the limited literature on 4IR in the education sector, particularly in Africa.
Keywords: 650; 4th industrial revolution (4IR); higher education; industry 4.0; teaching and learning; technology innovations; workforce